2022
DOI: 10.1371/journal.pgen.1009815
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and proteome profiling reveals complex adaptations of Candida parapsilosis cells assimilating hydroxyaromatic carbon sources

Abstract: Many fungal species utilize hydroxyderivatives of benzene and benzoic acid as carbon sources. The yeast Candida parapsilosis metabolizes these compounds via the 3-oxoadipate and gentisate pathways, whose components are encoded by two metabolic gene clusters. In this study, we determine the chromosome level assembly of the C. parapsilosis strain CLIB214 and use it for transcriptomic and proteomic investigation of cells cultivated on hydroxyaromatic substrates. We demonstrate that the genes coding for enzymes an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 101 publications
(158 reference statements)
0
1
0
Order By: Relevance
“…Transcriptomic and proteomic profiles have been widely used in the analysis of C. parapsilosis infections [28].Transcriptomics profiling during NAC exposure showed that the response of C. parapsilosis was quite extensive, mainly including the activation of biological processes such as regulation of biological, metabolic and cellular processes, cellular components and molecular function (Fig. 5a).…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptomic and proteomic profiles have been widely used in the analysis of C. parapsilosis infections [28].Transcriptomics profiling during NAC exposure showed that the response of C. parapsilosis was quite extensive, mainly including the activation of biological processes such as regulation of biological, metabolic and cellular processes, cellular components and molecular function (Fig. 5a).…”
Section: Discussionmentioning
confidence: 99%